2021
DOI: 10.3390/children8050348
|View full text |Cite
|
Sign up to set email alerts
|

“Difficult to Sedate”: Successful Implementation of a Benzodiazepine-Sparing Analgosedation-Protocol in Mechanically Ventilated Children

Abstract: We sought to evaluate the success rate of a benzodiazepine-sparing analgosedation protocol (ASP) in mechanically ventilated children and determine the effect of compliance with ASP on in-hospital outcome measures. In this single center study from a quaternary pediatric intensive care unit, our objective was to evaluate the ASP protocol, which included opiate and dexmedetomidine infusions and was used as first-line sedation for all intubated patients. In this study we included 424 patients. Sixty-nine percent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Regular spontaneous awakening and breathing trials with pause in all sedation have been successful in reducing time on mechanical ventilation, length of PICU-stay and cumulative dosis of sedatives ( 45 ), but have not been proven effective in terms of short-term health related quality of life ( 48 ). Instead, compared to use of standardized sedation protocols with continuous reduction in sedation ( 40 , 49 ), Vet et al ( 50 ) showed daily sedation interruption in addition to protocolized sedation to increase mortality in critically ill children when compared to those under protocolized sedation only. There were no added benefits for clinical outcome in the combined group.…”
Section: Resultsmentioning
confidence: 99%
“…Regular spontaneous awakening and breathing trials with pause in all sedation have been successful in reducing time on mechanical ventilation, length of PICU-stay and cumulative dosis of sedatives ( 45 ), but have not been proven effective in terms of short-term health related quality of life ( 48 ). Instead, compared to use of standardized sedation protocols with continuous reduction in sedation ( 40 , 49 ), Vet et al ( 50 ) showed daily sedation interruption in addition to protocolized sedation to increase mortality in critically ill children when compared to those under protocolized sedation only. There were no added benefits for clinical outcome in the combined group.…”
Section: Resultsmentioning
confidence: 99%
“…In our unit, before the implementation of the LiberAction, delirium screening was never performed, early mobilization was not protocolized and sedation was mainly based on benzodiazepine, therefore, an extensive educational process of all PICU staff was needed to address important knowledge gaps ( 15 ). Compared with other similar quality improvement projects ( 12 , 15 , 21 , 33 ), our educational process was relatively short (8 months), however, this time was sufficient to implement simultaneously all the three components of the PICU liberation bundle and achieve good results in terms of bundle adherence and patients' safety. These good achievements were possible mainly for two reasons: (a) the “ in situ training” performed at the McMaster PICU in 2019 and (b) the limited number of PICU staff to be educated and trained.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines have been the mainstay of pediatric sedation for many decades, however, in recent years a causal and temporal relationship was demonstrated between benzodiazepine exposure and delirium development ( 21 , 29 ). The LiberAction project successfully implemented a benzodiazepine sparing sedation protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations